Effect of solid-state fermentation and drying methods on the physicochemical properties of flour of two plantain cultivars grown in Malaysia - Olaniyi, Lasekan Olusegun; Morolayo, Shittu Rafiat (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The present work assessed the effect of solid-state fermentation (SSF) and drying methods [hot air drying (HAD) and hot air drying assisted by microwave finish drying (MFD)] on the physicochemical, functional and gelatinisation properties of flours of Nangka and Tanduk plantain cultivars. Drying methods and SSF did not affect the fat, dietary fibre and carbohydrate contents of the plantain flours. However, both treatments significantly affected the pH and titratable acidity of the flours. In addition, SSF coupled with MFD significantly increased the water absorption and oil absorption capacities of the flours more than the flours obtained from the hot air drying. Similar trend was observed with the swelling characteristics of the flours. Fermented and MFD flours had higher swelling power than flours obtained by hot air drying. Optical microscopy revealed that drying methods employed in the present work did not significantly alter the starch granules birefringence of the plantains.